Ammonium and Sulfate Assimilation Is Widespread in Benthic Foraminifera - LeKieffre, Charlotte; Jauffrais, Thierry; Bernhard, Joan M.; Filipsson, Helena L.; Schmidt, Christiane; Roberge, Hélène; Maire, Olivier; Panieri, Giuliana; Geslin, Emmanuelle; Meibom, Anders (Frontiers in Marine Science, 2022)
Nitrogen and sulfur are key elements in the biogeochemical cycles of marine ecosystems to which benthic foraminifera contribute significantly. Yet, cell-specific assimilation of ammonium, nitrate and sulfate by these protists is poorly characterized and understood across their wide range of species-specific trophic strategies. For example, detailed knowledge about ammonium and sulfate assimilation pathways is lacking and although some benthic foraminifera are known to maintain intracellular pools of nitrate and/or to denitrify, the potential use of nitrate-derived nitrogen for anabolic processes has not been systematically studied. In the present study, NanoSIMS isotopic imaging correlated with transmission electron microscopy was used to trace the incorporation of isotopically labeled inorganic nitrogen (ammonium or nitrate) and sulfate into the biomass of twelve benthic foraminiferal species from different marine environments. On timescales of twenty hours, no detectable 15N-enrichments from nitrate assimilation were observed in species known to perform denitrification, indicating that, while denitrifying foraminifera store intra-cellular nitrate, they do not use nitrate-derived nitrogen to build their biomass. Assimilation of both ammonium and sulfate, with corresponding 15N and 34S-enrichments, were observed in all species investigated (with some individual exceptions for sulfate). Assimilation of ammonium and sulfate thus can be considered widespread among benthic foraminifera. These metabolic capacities may help to underpin the ability of benthic foraminifera to colonize highly diverse marine habitats.